Defects and Interfaces on PtPb Nanoplates Boost Fuel Cell Electrocatalysis. Issue 3 (22nd November 2017) - Sun, Yingjun; Liang, Yanxia; Luo, Mingchuan; Lv, Fan; Qin, Yingnan; Wang, Lei; Xu, Chuan; Fu, Engang; Guo, Shaojun
Abstract: Nanostructured Pt is the most efficient single‐metal catalyst for fuel cell technology. Great efforts have been devoted to optimizing the Pt‐based alloy nanocrystals with desired structure, composition, and shape for boosting the electrocatalytic activity. However, these well‐known controls still show the limited ability in maximizing the Pt utilization efficiency for achieving more efficient fuel cell catalysis. Herein, a new strategy for maximizing the fuel cell catalysis by controlling/tuning the defects and interfaces of PtPb nanoplates using ion irradiation technique is reported. The defects and interfaces on PtPb nanoplates, controlled by the fluence of incident C + ions, make them exhibit the volcano‐like electrocatalytic activity for methanol oxidation reaction (MOR), ethanol oxidation reaction (EOR), and oxygen reduction reaction (ORR) as a function of ion irradiation fluence. The optimized PtPb nanoplates with the mixed structure of dislocations, subgrain boundaries, and small amorphous domains are the most active for MOR, EOR, and ORR. They can also maintain high catalytic stability in acid solution. This work highlights the impact and significance of inducing/controlling the defects and interfaces on Pt‐based nanocrystals toward maximizing the catalytic performance by advanced ion irradiation strategy. Abstract : A novel strategy for achieving efficient fuel cell catalysis by tuning/controlling defects and interfaces on PtPb nanoplates using ion irradiation technique is demonstrated. The nanoplates transforme from single crystal to polycrystal with varying degrees of dislocations, subgrain boundaries and partial amorphization by controlling the ion fluence. Such interesting strategy enables them exhibit the volcano‐like electrocatalytic activity for fuel cell performance.